Increased dietary Trp, Thr, and Met supplementation improves growth performance and protein deposition of salmonella-challenged growing pigs under poor housing conditions - da Cunha Valini, Graziela Alves [UNESP]; Arnaut, Pedro Righetti [UNESP]; França, Ismael [UNESP]; Ortiz, Manoela Trevisan [UNESP]; de Oliveira, Marllon José Karpeggiane [UNESP]; Melo, Antonio Diego Brandão [UNESP]; Marçal, Danilo Alves [UNESP]; Campos, Paulo Henrique Reis Furtado; Htoo, John Khun; Brand, Henrique Gastmann; Hauschild, Luciano [UNESP] (Oxford University Press (OUP), 2023)
Highly intensified rearing conditions and precarious sanitary management predispose pigs to immune system activation, altered amino acid (AA) metabolism, and decreased growth performance. Thus, the main objective of this study was to evaluate the effects of increased dietary tryptophan (Trp), threonine (Thr), and methionine + cysteine (Met + Cys) supplementation on performance, body composition, metabolism, and immune responses of group-housed growing pigs under challenging sanitary conditions. A hundred and twenty pigs (25.4 ± 3.7 kg) were randomly assigned to a 2 × 2 factorial arrangement, consisting of two sanitary conditions (SC, good [GOOD] or salmonella-challenge and poor housing condition [Salmonella Typhimurium (ST) + POOR]) and two diets, control (CN) or supplemented with AA (Trp, Thr, and Met + Cys:Lys ratios 20% higher than those of the CN diet [AA>+]). Pigs were followed during the growing phase (25-50 kg) and the trial lasted 28 d. The ST + POOR SC pigs were challenged with Salmonella Typhimurium and raised in a poor housing condition. The ST + POOR SC increased rectal temperature, fecal score, serum haptoglobin, and urea concentration (P < 0.05) and decreased serum albumin concentration (P < 0.05) compared with GOOD SC. Body weight, average daily feed intake, average daily gain (ADG), feed efficiency (G:F), and protein deposition (PD) were greater in GOOD SC than in ST + POOR SC (P < 0.01). However, pigs housed in ST + POOR SC fed with AA+ diet had lower body temperature (P < 0.05), increased ADG (P < 0.05) and nitrogen efficiency (P < 0.05), and a tendency for improved PD and G:F (P < 0.10) compared with CN diet fed pigs. Regardless of the SC, pigs fed AA+ diet had lower serum albumin (P < 0.05) and tended to decrease serum urea levels (P < 0.10) compared with CN diet. The results of this study suggest that the ratio of Trp, Thr, and Met + Cys to Lys for pigs are modified by sanitary conditions. Furthermore, supplementation of diets with a blend of Trp, Thr, and Met + Cys improves performance, especially under salmonella-challenge and poor housing conditions. Dietary tryptophan, threonine, and methionine supplementation can modulate immune status and influence resilience to sanitary challenges.
Keywords: amino acids; body composition; immune system; inflammation; swine